Biological monitoring of kidney function among workers occupationally exposed to trichloroethylene. Issue 4 (18th March 2004) - Green, T; Dow, J; Ong, C N; Ng, V; Ong, H Y; Zhuang, Z X; Yang, X F; Bloemen, L
Abstract : Aims: To investigate the nephrotoxic potential of trichloroethylene in a currently exposed population using sensitive urinary markers of kidney toxicity. Methods: Renal dysfunction was monitored in a cross-sectional study of 70 workers currently exposed to trichloroethylene. An age and sex matched control population of 54 individuals was drawn from hospital and administrative staff. Results: The mean exposure to trichloroethylene, estimated from urinary trichloroacetic acid concentrations, was 32 ppm (range 0.5–252 ppm) with an average duration of exposure of 4.1 years (range 1–20 years). Significant differences between the exposed and control populations were found for nephrotoxicity markers N-acetylglucosaminidase (NAG) and albumin, and for the mode of action marker, formic acid. However, neither NAG nor albumin showed a significant correlation with either the magnitude or duration of exposure to trichloroethylene. There was a significant correlation between urinary formic acid and trichloroacetic acid concentrations. Within the exposed population there were dose dependent increases in urinary methylmalonic acid concentrations and urinary glutathione S-transferase α activity. Although still within the control range, these changes were clearly dose dependent and consistent with one of the proposed mechanisms of trichloroethylene induced kidney toxicity. Conclusion: Although there was no evidence of kidney toxicity within the population studied, the results suggest that kidney damage could occur at exposure concentrations higher (>250 ppm) than those encountered in this study.